Search for resonant t̄t production in lepton+jets events in pp collisions at √s=7 TeV - Chatrchyan, S. (2012)
A model-independent search for the production of heavy resonances decaying into top-antitop quark pairs is presented. The search is based on events containing one lepton (muon or electron) and at least two jets selected from data samples corresponding to an integrated luminosity of 4.4-5.0 fb -1 collected in pp collisions at √s =7 TeV. Results are presented from the combination of two dedicated searches optimized for boosted production and production at threshold. No excess of events is observed over the expected yield from the standard model processes. Topcolor Z′ bosons with narrow (wide) width are excluded at 95% confidence level for masses below 1.49 (2.04) TeV and an upper limit of 0.3 (1.3) pb or lower is set on the production cross section times branching fraction for resonance masses above 1 TeV. Kaluza-Klein excitations of a gluon with masses below 1.82 TeV (at 95% confidence level) in the Randall-Sundrum model are also excluded, and an upper limit of 0.7 pb or lower is set on the production cross section times branching fraction for resonance masses above 1 TeV.[Figure not available: See fulltext.] © 2012 CERN for the benefit of the CMS collaboration.